2016
DOI: 10.1016/j.ejso.2016.05.024
|View full text |Cite
|
Sign up to set email alerts
|

Variation in the management of ductal carcinoma in situ in the UK: Results of the Mammary Fold National Practice Survey

Abstract: General rightsThis document is made available in accordance with publisher policies. Please cite only the published version using the reference above. Full terms of use are available: http://www.bristol.ac.uk/pure/about/ebr-terms

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 28 publications
(27 reference statements)
0
6
0
Order By: Relevance
“…Besides positive excision margins, other risk factors for recurrence after BCS are tumour grade and size; patients with higher grade and/or larger DCIS appear at higher risk of developing IBC or recurrent DCIS after lumpectomy [22,23]. A recent UK-wide survey found these are the two most common factors in decision-making for adjuvant radiotherapy (in 51.3 and 35.5% of sites surveyed, respectively [24]). Additional independent predictors of progression or recurrence are younger patient age, micropapillary architecture and the presence of comedonecrosis [23,[25][26][27][28], as well as African-American race and strong family history of breast cancer or BRCA1/2 mutation [27].…”
Section: Adjuvant Therapymentioning
confidence: 99%
See 2 more Smart Citations
“…Besides positive excision margins, other risk factors for recurrence after BCS are tumour grade and size; patients with higher grade and/or larger DCIS appear at higher risk of developing IBC or recurrent DCIS after lumpectomy [22,23]. A recent UK-wide survey found these are the two most common factors in decision-making for adjuvant radiotherapy (in 51.3 and 35.5% of sites surveyed, respectively [24]). Additional independent predictors of progression or recurrence are younger patient age, micropapillary architecture and the presence of comedonecrosis [23,[25][26][27][28], as well as African-American race and strong family history of breast cancer or BRCA1/2 mutation [27].…”
Section: Adjuvant Therapymentioning
confidence: 99%
“…In short, the VNPI has not been shown unequivocally to be of clinical utility and this has hindered its acceptance into clinical practice. The use of this tool has also lacked support in the UK [50], with a recent survey revealing that only 15.8% of breast units across the country use it routinely and even in these sites there is a lack of consistency in the scores applied in the decision-making process [24]. Table 1).…”
Section: Challenges In the Management Of Dcis: The Need For Predictivmentioning
confidence: 99%
See 1 more Smart Citation
“…It is anticipated that the majority of the 144 breast units in the UK will offer TM to their patients. Based on experience from the iBRA study [26] and other trainee collaborative projects [20], approximately 40% of units will choose to participate in the study. It is therefore anticipated that between 250 and 500 patients will be recruited to the study from approximately 50 centres over a six month period.…”
Section: Methods and Analysismentioning
confidence: 99%
“…[17], [18], [19] and MasDA (Mastectomy Decisions Audit) and the development of a national breast surgical research collaborative [20] have demonstrated that the methodology is both feasible and effective within the context of breast surgery. It is anticipated that this network of highly-motivated breast and plastic surgical trainees and consultants can be utilised to deliver a new study to determine the practice and outcomes of therapeutic mammaplasty in the UK.…”
Section: Introductionmentioning
confidence: 99%